2021
DOI: 10.1093/jamia/ocab199
|View full text |Cite
|
Sign up to set email alerts
|

The quality of social determinants data in the electronic health record: a systematic review

Abstract: Objective The aim of this study was to collect and synthesize evidence regarding data quality problems encountered when working with variables related to social determinants of health (SDoH). Materials and Methods We conducted a systematic review of the literature on social determinants research and data quality and then iteratively identified themes in the literature using a content analysis process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 64 publications
1
41
0
Order By: Relevance
“…Nevertheless, very few articles in the medical informatics and AI literature mention any aspects of SDoH in the context of AI fairness and bias, suggesting that SDoH considerations are not yet routine in the development of AI for health. A potential contributor to the lack of SDoH representation in datasets are limitations posed by EHR designs, poor data quality, and similar to intersectionality, challenges in operationalizing the complex concept of SDoH into a format that is amenable to documentation in EHRs [3,37]. Fluid definitions of SDoH and the lack of standards for the capture and representation of SDoH stand as substantial challenges [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, very few articles in the medical informatics and AI literature mention any aspects of SDoH in the context of AI fairness and bias, suggesting that SDoH considerations are not yet routine in the development of AI for health. A potential contributor to the lack of SDoH representation in datasets are limitations posed by EHR designs, poor data quality, and similar to intersectionality, challenges in operationalizing the complex concept of SDoH into a format that is amenable to documentation in EHRs [3,37]. Fluid definitions of SDoH and the lack of standards for the capture and representation of SDoH stand as substantial challenges [37].…”
Section: Discussionmentioning
confidence: 99%
“…Improved representation of the features of underrepresented population subgroups in datasets used for AI development is one component towards AI fairness. It is commonly suggested that improved and more complete capture of sensitive features of underrepresented groups (e.g., demographic characteristics) and social determinants of health (SDoH) in AI datasets are necessary towards the development of less biased algorithms [2,3]. Beyond providing a foundation for less biased algorithm development at the outset, diverse datasets are also necessary to enable computational approaches to mitigation of bias in AI; these approaches rely, to a large extent, on data quality.…”
Section: Introductionmentioning
confidence: 99%
“…Many SDH data included in the studies were obtained through EHRs. Despite widespread acknowledgement that SDH data are frequently missing or inaccurate in EHRs and large datasets (60), SDH data quality, including characteristics of completeness, correctness, and consistency, was seldom addressed in the studies included in this review-three out of four studies failed to report handling of missing data, and no study reported applying any validation method for SDH data. Measurement error may explain the mixed findings of independent associations between some SDH and postsepsis outcomes reported among our studies.…”
Section: Measurement Errormentioning
confidence: 99%
“…The health care standard only recommends a structure for how information about patient race and ethnicity should be stored; in practice, there are wide variations in how health care systems collect this information. Studies have documented that it is frequently missing from the patient record, and when it is collected, it is often of poor quality [18][19][20][21][22][23]. Our objective was to explore variations in how health care systems collect and report information about the race and ethnicity of their patients.…”
Section: Introductionmentioning
confidence: 99%